2011
DOI: 10.1007/s10549-011-1851-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential oxidative status and immune characterization of the early and advanced stages of human breast cancer

Abstract: Breast cancer is the malignant neoplasia with the highest incidence in women worldwide. Chronic oxidative stress and inflammation have been indicated as major mediators during carcinogenesis and cancer progression. Human studies have not considered the complexity of tumor biology during the stages of cancer advance, limiting their clinical application. The purpose of this study was to characterize systemic oxidative stress and immune response parameters in early (ED; TNM I and II) and advanced disease (AD; TNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 47 publications
5
72
0
3
Order By: Relevance
“…Under mild oxidative stress conditions, such as the one that is induced by the repression of mitochondrial β-F1-ATPase, GAPDH is strongly hyperactivated, while apoptogenic stress levels inhibit GAPDH activity [26,27]. In advanced stages of tumour progression, oxidative stress is higher than in early phases of carcinogenesis [28][29][30], which can explain the increased levels of GAPDH in stage I in comparison with later stages of progression. In addition, overexpression of GAPDH has two cooperative roles in protection towards caspase-independent cell death; a high glycolytic ATP production and the induction of autophagy-mediated clearance of damaged mitochondria [6,7], both of which favour tumour onset.…”
Section: Discussionmentioning
confidence: 99%
“…Under mild oxidative stress conditions, such as the one that is induced by the repression of mitochondrial β-F1-ATPase, GAPDH is strongly hyperactivated, while apoptogenic stress levels inhibit GAPDH activity [26,27]. In advanced stages of tumour progression, oxidative stress is higher than in early phases of carcinogenesis [28][29][30], which can explain the increased levels of GAPDH in stage I in comparison with later stages of progression. In addition, overexpression of GAPDH has two cooperative roles in protection towards caspase-independent cell death; a high glycolytic ATP production and the induction of autophagy-mediated clearance of damaged mitochondria [6,7], both of which favour tumour onset.…”
Section: Discussionmentioning
confidence: 99%
“…Using deferoxamine-mediated chelation, appropriate temperature, and sufficient incubation time, it will be potentially possible to assess the impact of iron with thrombelastography, thromboelastimetry, or SEM. Thus, as reviewed [1], the role of ferritin and free iron excess in chronic diseases such as diabetes mellitus, rheumatoid arthritis, or perhaps cancer [19] can be assessed. Perhaps the degree of iron-specific hypercoagulability could be correlated with clinical disease, and in turn, such diagnostics could be used to assess the effectiveness of therapy targeted at diminishing circulating iron concentrations or interventions that diminish inflammatory processes that result in iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the uric acid level is depleted during tumor development (47,48). In contrast, uric acid may be increased due to cancer therapy, such as by chemotherapy or irradiation during treatment.…”
Section: Cancer Patients Healthy Controls ---------------------------mentioning
confidence: 99%